The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1210/jc.2015-2230
|View full text |Cite
|
Sign up to set email alerts
|

Urine Albumin-to-Creatinine Ratio: A Marker of Early Endothelial Dysfunction in Youth

Abstract: UACR is an early marker of endothelial dysfunction in youth, independent of glycemia. Endothelial dysfunction may mediate the link between obesity-related insulin resistance and early microalbuminuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…Another recent support argues that HbA1c is associated with low-grade albuminuria in Chinese adults, and it has been suggested that insulin resistance could result in endothelial dysfunction and the dysfunction of the glomerular capillary wall leading to albuminuria [10]. Bartz et al also demonstrated that the adiposity-related insulin resistance to endothelial function may impact renal dysfunction, and so UACR provides an early marker of endothelial dysfunction in obese adolescents [31]. Additionally, this study sought to perform the assessment of endothelial function by peripheral arterial tonometry, and suggests that endothelial dysfunction mediates the link between obesity-related insulin resistance and early microalbuminuria [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent support argues that HbA1c is associated with low-grade albuminuria in Chinese adults, and it has been suggested that insulin resistance could result in endothelial dysfunction and the dysfunction of the glomerular capillary wall leading to albuminuria [10]. Bartz et al also demonstrated that the adiposity-related insulin resistance to endothelial function may impact renal dysfunction, and so UACR provides an early marker of endothelial dysfunction in obese adolescents [31]. Additionally, this study sought to perform the assessment of endothelial function by peripheral arterial tonometry, and suggests that endothelial dysfunction mediates the link between obesity-related insulin resistance and early microalbuminuria [31].…”
Section: Discussionmentioning
confidence: 99%
“…Bartz et al also demonstrated that the adiposity-related insulin resistance to endothelial function may impact renal dysfunction, and so UACR provides an early marker of endothelial dysfunction in obese adolescents [31]. Additionally, this study sought to perform the assessment of endothelial function by peripheral arterial tonometry, and suggests that endothelial dysfunction mediates the link between obesity-related insulin resistance and early microalbuminuria [31]. The present study also suggests that insulin resistance may play an important role in the development of renal impairment in conjunction with central obesity, which was a crucial component of diagnosis of metabolic syndrome among children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Microalbuminuria, defined as albumin-to-creatinine ratio ≥30mg/g or an albumin-excretion-rate ≥200ug/min, has been used as a marker of renal and systemic vascular dysfunction (33) and metabolic risk in adults and adolescents with prediabetes and T2D (34), (35). The implications of having microalbuminuria are, however, controversial, since microalbuminuria regresses to normoalbuminuria in a significant proportion of adults with T2D (36).…”
Section: Risk Factors For Dkd In Youth With T2dmentioning
confidence: 99%
“…Additionally, obesity and impaired glucose tolerance are associated with renal injury that is pathophysiologically and histologically similar to classical diabetic nephropathy (2729, 51), suggesting that the renal insult may begin prior to the development of frank hyperglycemia (30). For example, a recent report demonstrated increased estimated GFR in adolescents with pre-diabetes and overweight adolescents compared to lean controls (35). …”
Section: Risk Factors For Dkd In Youth With T2dmentioning
confidence: 99%
“…MAU can play pivotal role in early detection of endothelial changes and CV risk, considering the positive association with FBS, BMI and BP. Precipitating factors of MAU should be managed via lifestyle modifications and medications as it is a reversible condition [14,15]. Thus obese young and middle aged adults should be screened regularly.…”
Section: Discussionmentioning
confidence: 99%